2006
DOI: 10.2527/jas.2005-634
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus appetite in sheep: Dissociating taste from postingestive effects1,2

Abstract: We hypothesized that lambs discriminate the postingestive effects of P and associate those effects with feed flavor to modify feed choices. Three predictions were tested based on this hypothesis: 1) lambs will modify preference for arbitrary flavors eaten during intraruminal infusions of NaH2PO4, 2) changes in preferences are more specific than changes in osmotic load induced by salts of Na; and 3) preference for P is inversely related to the concentration of inorganic P in blood. Thirty lambs were depleted of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Animals are thought to respond to excesses, deficits, or imbalances of nutrients (Villalba et al, 2006). Birds have been shown to possess Ca sensors (T1R3 and Ca sensing receptor), but it is yet to be determined whether they mediate Ca appetite or taste (Tordoff et al, 2008;Roura et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Animals are thought to respond to excesses, deficits, or imbalances of nutrients (Villalba et al, 2006). Birds have been shown to possess Ca sensors (T1R3 and Ca sensing receptor), but it is yet to be determined whether they mediate Ca appetite or taste (Tordoff et al, 2008;Roura et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, animals maintain a balance of energy to protein that meets their nutritional needs, and in the process, they associate different internal states with the ingestion, or lack thereof, of different nutrients (Egan, 1980;Kyriazakis and Oldham, 1993). Likewise, lambs deficient in phosphorus and calcium increase preferences for flavours and supplements that provide those minerals (Villalba et al, 2006a;J. Villalba, unpublished results).…”
Section: Self-medication In Herbivoresmentioning
confidence: 99%
“…The literature has widely reported that sheep can develop conditioned food aversions or preferences when either negative (Du Toit et al, 1991;Ralphs et al, 1995;Kyriazakis et al, 1997) or positive (Buritt and Provenza, 1992;Arsenos and Kyriazakis, 1999;Villalba et al, 2006) post-ingestive consequences are associated with that food. Recently, introduction of straw in the rumen (Baumont et al, 2007) or distension with a balloon (Villalba et al, 2009a and2009b) were used to demonstrate that rumen fill is perceived as a negative post-ingestive signal, leading to a decreased preference for the associated forage.…”
Section: Short-term Choices: Effect Of Recent Dietary Experiencesmentioning
confidence: 99%